2021
DOI: 10.1016/j.jneuroim.2021.577654
|View full text |Cite
|
Sign up to set email alerts
|

N-acylethanolamine regulation of TLR3-induced hyperthermia and neuroinflammatory gene expression: A role for PPARα

Abstract: Increasing evidence suggests that SARS-CoV-2, the virus responsible for the COVID-19 pandemic, is associated with increased risk of developing neurological or psychiatric conditions such as depression, anxiety or dementia. While the precise mechanism underlying this association is unknown, aberrant activation of toll-like receptor (TLR)3, a viral recognizing pattern recognition receptor, may play a key role. Synthetic cannabinoids and enhancing cannabinoid tone via inhibition of fatty acid amide hydrolase (FAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This seems to be confirmed by the results of the present study, which indicate significantly less activation of PPARγ in the case of co-infection than in the case of TBEV infection alone. In contrast to other viral diseases such as COVID-19, it has been suggested that OEA, which is also upregulated only in TBE patients, is responsible for the downregulation of NFκB-related gene expression [ 52 ] and also modulates the effects partially mediated by PPARα [ 53 ]. In addition, in patients with COVID-19, it was found that activation of the endocannabinoid system reduces viral replication and the level of pro-inflammatory cytokines [ 54 ], hence a similar response of the endocannabinoid system, especially in the case of TBE, but also partially in co-infections, can be considered beneficial and even pro- survival effect on the infected organism.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be confirmed by the results of the present study, which indicate significantly less activation of PPARγ in the case of co-infection than in the case of TBEV infection alone. In contrast to other viral diseases such as COVID-19, it has been suggested that OEA, which is also upregulated only in TBE patients, is responsible for the downregulation of NFκB-related gene expression [ 52 ] and also modulates the effects partially mediated by PPARα [ 53 ]. In addition, in patients with COVID-19, it was found that activation of the endocannabinoid system reduces viral replication and the level of pro-inflammatory cytokines [ 54 ], hence a similar response of the endocannabinoid system, especially in the case of TBE, but also partially in co-infections, can be considered beneficial and even pro- survival effect on the infected organism.…”
Section: Discussionmentioning
confidence: 99%
“…Where PEA is also able to inhibit SARS-CoV-2 entry and replication ( 50 ). Interestingly, others have identified PPAR-α as a potential mediator neuroinflammation in COVID-19 ( 51 ). The third Top pathway had peak gene FAM89B, representing TGFβ signalling pathway, which is also associated with pulmonary fibrosis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, famotidine, a specific histamine H2 receptor antagonist, can inhibit TLR3 expression in SARS-CoV-2 infected cells and reduce TLR3-dependent NF-κB and IRF3 signaling, subsequently controlling antiviral and inflammatory responses ( Mukherjee et al, 2021 ) and reducing the risk of intubation and death in hospitalized patients with COVID-19 ( Freedberg et al, 2020 ). Another TLR signaling inhibitor, the PPARα agonist oleoylethanolamide (OEA), was reported to attenuate TLR3-induced hyperthermia and reduce the expression of hyperthermia-related genes including IL-1β, iNOS, COX2, and m-PGES in the hypothalamus ( Flannery et al, 2021 ).…”
Section: Toll-like Receptor Signaling Inhibitors Protect Against Hype...mentioning
confidence: 99%